EGCG binds intrinsically disordered N-terminal domain of p53 and disrupts p53-MDM2 interaction - Jing Zhao (Nature Portfolio, 2021)
Epigallocatechin gallate (EGCG) is a catechin flavonoid which induces apoptosis in cancerous cells, but the underlying molecular mechanisms remain poorly understood. Here authors use an interdisciplinary approach to show a direct interaction between EGCG and the tumor suppressor p53 and demonstrate that EGCG inhibits ubiquitination of p53 by MDM2.